Java language - Dr. Mourad Brik (University of M'sila, 2024)
This handout is meticulously crafted to cater to the specific needs of second-year master's students in programming skills, providing a comprehensive exploration of Java's capabilities. From simple concepts to intricate advanced data structures, each chapter is designed to enhance the student’s proficiency in Java, equipping them with skills that needed to attain a proficient level in Java programming, which enabling them to effectively tackle the modern technology facet
Keywords: Java; OOP; Compiler; interpreter